2008
DOI: 10.1074/jbc.m707478200
|View full text |Cite
|
Sign up to set email alerts
|

Linoleic Acid Induces Calcium Signaling, Src Kinase Phosphorylation, and Neurotransmitter Release in Mouse CD36-positive Gustatory Cells

Abstract: We have recently demonstrated that the cells expressing CD36, localized apically on the taste buds of mouse lingual circumvallate papillae, act as gustatory cells. In the present study we isolated these CD36-positive cells from mouse circumvallate papillae and investigated intracellular signaling events, triggered by a long-chain polyunsaturated fatty acid, i.e. linoleic acid (LA). LA induced increases in free intracellular calcium concentrations, [Ca 2؉ ] i , by recruiting calcium from endoplasmic reticulum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
136
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(155 citation statements)
references
References 38 publications
14
136
0
4
Order By: Relevance
“…In isolated hypothalamic ventromedial nucleus neurons, the addition of oleic acid resulted in alterations of intracellular calcium oscillations, and these effects were reduced by the CD36 inhibitor SSO (67). More evidence for a link between CD36 and cellular calcium was obtained using taste bud cells sorted based on CD36 expression (68). It was shown that exposure of CD36-positive cells to extracellular linoleate increased intracellular calcium through 1,4,5-trisphosphate-mediated release of ER calcium.…”
Section: Discussionmentioning
confidence: 83%
“…In isolated hypothalamic ventromedial nucleus neurons, the addition of oleic acid resulted in alterations of intracellular calcium oscillations, and these effects were reduced by the CD36 inhibitor SSO (67). More evidence for a link between CD36 and cellular calcium was obtained using taste bud cells sorted based on CD36 expression (68). It was shown that exposure of CD36-positive cells to extracellular linoleate increased intracellular calcium through 1,4,5-trisphosphate-mediated release of ER calcium.…”
Section: Discussionmentioning
confidence: 83%
“…CD36, in particular, seems to play a key role in fatty acid detection. ElYassimi et al 124 showed that linoleic acid binds to mouse gustatory cells that express CD36, triggering the release of noradrenaline and 5-hydroxytryptamine via calcium signaling. The large interindividual variation in the ability to detect oral fatty acids likely affects food intake and weight.…”
Section: Macronutrient Selectionmentioning
confidence: 99%
“…De plus, nous avons démontré chez la souris que, en réponse à l'interaction entre les AGLC et le CD36 au niveau des TRC, le CD36 est couplé à la phosphorylation de tyrosines kinases de la famille Src (Fyn-p 59 et Yes-p 62 ) [7]. Nous avons constaté que les AGLC induisent également une augmentation de la concentration de Ca 2+ intracellulaire ([Ca 2+ ]i) dans les TRC [8].…”
Section: Cd36 Un Récepteur De Lipides Impliqué Dans La Détection Orounclassified
“…Ce phénomène est strictement dépendant de CD36 car la signalisation calcique est fortement réduite en présence d'un inhibiteur pharmacologique de la liaison des AGLC à CD36 [8]. Cette augmentation du [Ca 2+ ]i semble résulter d'une mobilisation du calcium du réti-culum endoplasmique (RE) via la production d'inositol triphosphate (IP 3 ) et de l'ouverture des canaux SOC (storeoperated calcium) [7]. Cependant, les mécanismes impliqués dans l'ouverture des canaux SOC des cellules gustatives restaient encore non définis.…”
Section: Cd36 Un Récepteur De Lipides Impliqué Dans La Détection Orounclassified